A Pregnant female with renal mass : A case report study and review of literature . - Farhan, Saad Dakhil; F. Ridha, Amina (Journal of the Faculty of Medicine Baghdad, 2022)
Abstract Back ground: Renal cell carcinoma is an uncommon condition that develops during pregnancy. Due to a lack of conventional norms and a dearth of literature, its management is a serious issue. Case presentation: We will discuss a case study of a twenty-year-old female girl who is pregnant G1 P1 A0, has had five missing periods (20 weeks gestation), and has frank hematuria due to a massive, incidentally detected renal cell carcinoma. We also go through the current guidelines for treating kidney malignancies during pregnancy, as well as the imaging studies that are now available. Conclusion: Although the best time for surgery is debatable, a multi-disciplinary team must make the decision. A detailed and thorough discussion with the mother, as well as an explanation of the predicted hazards for each treatment modality, is essential in regards to her wishes and concerns about fetal safety.